PENGEMBANGAN BAHAN AJAR MATERI PERSAMAAN KUADRAT BERBANTUAN RUMUS CEPAT - Nur Kesumayanti; Rizki Wahyu Yunian Putra (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2017)
ABSTRACTThe purpose of this research is to produce material of quadratic equations supported by quick, appealing, and easy formula for students. The Method of This research is Research and Development Procedure ( R D)  from Brog and Gall which is adopted by Sucipto that is up to the seventh stage, such as: potential problem, data collection, product design, design validation, design revision, product trial, and product revisions. The subject of this research is one of high school students in Bandar Lampung. The data collection was obtained from the validation of the instruments as well as trials of small group and large group products. This researchs analyzed by descriptive quantitative and qualitative. The products produced through the validation of the feasibility of  the material expert validator team, the media expert, the linguist and the mathematic teacher and the language teacher obtained the criteria "Very worthy of use". furthermore on the aspects of small group and large group product trial obtained the criteria "Very easy and very interesting for students". Based on the results of assessment of responses by experts, teachers, and student responses it can be concluded that the material module of quadratic equations aided by the formula is quickly categorized very feasible, very interesting, and very easy for students.Keywords: Teaching Materials, Quadratic Equations, Quick Formulas